Analisis Karakteristik Penumpang Kereta Cepat Jakarta Bandung (Whoosh) di Stasiun Halim - Fadhil, Dimas Nu'Man; Siahaan, Langas Denny; Shandy, Antika Tiara (Jurnal Sistem Transportasi & Logistik, 2023)
In Indonesia, a new rail-based transportation mode has recently been introduced, namely the Jakarta-Bandung High-Speed Rail (KCJB), commonly known as "Whoosh." Whoosh connects the Jakarta area with Bandung, and the construction of the Jakarta-Bandung HighSpeed Rail is one of the international cooperation projects between Indonesia and China in the transportation sector. Because of that the author want to research the characteristics of passengers of the Jakarta-Bandung High-Speed Rail (Whoosh) at Halim Station, using quantitative methods and descriptive analysis to explain the characteristics of Whoosh passengers in terms of social demographics, economy, and travel patterns. In this study, the author uses 208 samples as research subjects. The passenger characteristics based on social demographics show that the majority are female, aged 21-35 years, students, with an average educational background of a bachelor’s degree (S1). The passenger characteristics based on economic factors indicate that the average monthly income is less than IDR 5,000,000. The passenger characteristics based on travel patterns reveal that the majority of passengers come from East Jakarta, stop at Padalarang Station, and continue their journey to Bandung City during holidays or weekends.